Performance metric analysis of modified LEACH routing protocol in wireless sensor network - Priyadarshi, Raghul; Tripathi, Hitesh; Bhardwaj, Abhyuday; Thakur, Ankush (International Journal of Engineering and Technology, 2017)
The lifetime of a network is reflected as one of the vital concerns in wireless sensor network because of a huge number of nodes and further its density and distribution. When the network size increases then routing protocol becomes one of the crucial issues that which routing protocol one should use so that network lifetime to be enhanced. Furthermore, sensor nodes must be alive to promise that network process must continue without any interruption or any loss of data in the network. In fact, there are a lot of clustering method is there to augment the network lifetime. But in this paper, presented routing protocol that is based on existing LEACH protocol called as K-mean clustering routing (KLEACH). Simulation results show that efficiency of the network has been improved and network lifetime has been also enhanced compared to existing LEACH protocol. Network lifetime of KLEACH protocol is almost increased by 40% and energy consumption is also decrease by almost 38% which reflects the good agreement of KLEACH algorithm compared to existing algorithm.